Geospatial Distribution of Public Secondary in Gombe Local Government Area, Gombe State of Nigeria - Caiaphas Makadi, Yila; Stephen Sati, abecca; Dankaka, Ismail (Universitas Terbuka, 2019)
The paper reviews research tradition of accessibility level and spatial distribution of student in public secondary school in gombe local government area, Gombe state. Primary and secondary data were used for the study. Primary data was collected using questionnaire and a hand-held GPS receiver to capture the coordinate points of schools and other relevant data. Secondary data include administrative map, population figures of both students and Teachers, Names and addresses of the secondary schools in the study area. The data were analyzed using geographic information techniques. From the data survey carried out, the result of the analysis showed the accessibility level and spatial distribution of school in Gombe were seventeen (17) public senior secondary and total number of students were nineteen thousand and eleven (19,011). The nearest neighbor analysis (NNA) for the spatial pattern of school were carried out based on each ward in study area which as ten (10) wards in each ward revealed two major spatial distributions. The spatial pattern of the Gombe LGA has Nearest Neighbour Ratio (NNR): 3.385087, Bolari East ward with NNR: 3.385087 and Shamaki wards NNR: 1.600148, which showed dispersed pattern, while Jekada Fari ward with NNR: 0.214890, Pantami ward with NNR: 0.226863, and Herwo Gana wards with NNR: 0.185239, were showed clustered pattern. The nearest neighbor index shows clustered pattern for all the wards in the local government area except Bolari East and Shamaki wards that has dispersed pattern of distribution. The implication of these two patterns means that accessibility is poor in the study area. Students travel than normal to overcome the function of distance.